Tindak Pidana Terhadap Kesusilaan Yang Dilakukan Tokoh Masyarakat Dari Sudut Pandang Kriminologi - Hartanto Hartanto (Universitas Muhammadiyah Gresik, 2020)
Crime continues to develop along with the development of society in all fields: political, economic, social, cultural and technological. Almost every day in the newspaper news, as well as electronic media, there is news about criminal acts against decency committed by various groups. Why it happened and how to overcome it is something that will be examined by the author. Cases of sexual decency against women, generally occur because of the imbalance of power relations in question is between men and women, and can also occur because of the imbalance of someone's